The State of Breast Cancer Reconstruction in Virginia: An Evidence-Based Framework for Identifying Locoregional Health Disparities. Issue 4 (October 2022) - Liston, Jared M.; Samuel, Ankhita; Camacho, T. Fabian; Anderson, Roger T.; Campbell, Chris A.; Stranix, John T.
Abstract : Background: Age, race, socioeconomic status, and proximity to plastic surgeons have been shown to impact receipt of reconstruction after mastectomy in several national studies. Given that targeted outreach efforts and programs to address these discrepancies would occur locoregionally, investigation of these reconstructive trends on a state level is warranted. Study Design: Patients diagnosed with breast cancer in Virginia between 2000 and 2018 were identified in the Virginia Department of Health Cancer Registry. Patients who underwent mastectomy breast conservation surgery, and/or breast reconstruction at the time of oncologic surgery were identified. Patient demographics were analyzed, and logistic regression analyses were used to determine the likelihood of receipt of mastectomy, receipt of mastectomy versus breast conservation surgery, receipt of mastectomy with reconstruction versus mastectomy alone, and receipt of mastectomy with reconstruction versus breast conservation surgery with respect to the demographic variables. Geographically weighted regression analyses were also performed to determine impact of geographic location on receipt of mastectomy and reconstruction after mastectomy. Results: A total of 78, 682 patients in Virginia underwent surgical treatment for breast cancer between 2000 and 2018. Living outside a metropolitan area, increased age, lower socioeconomic status, non-White race, and lower number of plastic surgeons within 50 miles were associated with decreased rates of postmastectomy reconstruction. Rural setting, lower socioeconomic status, and lower plastic surgeon supply were also associated with decreased rates of breast conservation surgery. Reconstruction after mastectomy was lowest in the northwest, central, and southwest regions of Virginia. Conclusions: Within the state of Virginia, programs to improve access to breast reconstruction for patients residing in rural regions, as well as non-White patients, older patients, and those in lower socioeconomic groups should be implemented. Future studies would implement and study the efficacy of such outreach programs, which could then be applied and tailored to other states or regions to address sociodemographic disparities in access to breast reconstruction.